Surgical management of Ludwig’s angina under conscious sedation using intravenous combination of dexmedetomidine and ketamine - Paliwal, Naresh; Pendam, Vibha; Lawhale, Sunil; Deshpande, Nandini (Asian Journal of Medical Sciences, 2023)
Background: Ludwig’s angina (LA) is a life-threatening condition, in which there is gangrenous cellulitis of floor of mouth that spreads through facial planes to involve neck region and has the potential to cause airway obstruction. Even though with advent of broad-spectrum antibiotics, it’s incidence has decreased considerably, the anesthetic management of patients, particularly children, undergoing drainage for LA group STILL remains a challenging task. Aims and Objectives: The aim of this study was to test the efficacy and safety of intravenous combination of dexmedetomidine and ketamine (DEXKET) for the drainage of abscess in patients having LA. Materials and Methods: This was a prospective study, in which 40 cases having LA and posted for Abscess drainage were included on the basis of a redefined inclusion and exclusion criteria. Abscess drainage was done under anesthesia using DEXKET as the only intravenous drug. DEXKET was prepared by mixing dexmedetomidine 0.5 mcg/kg along with ketamine 1 mg/kg in a 5 ml syringe and then diluted until 5 ml with distilled water. This was given as bolus dose. Drainage was accomplished under IV (DEXKET) sedation. Results: In this study, there were 28 males and 12 females with a M: F ratio of 1:0.42. The mean age of male and female patients was found to be 38.35±10.58 and 36.41±11.37 years, respectively. Dental caries was the most common cause leading to LA which was seen in 32 (80%) patients. There were no episodes of significant bradycardia, hypotension or desaturation during surgical procedure, as well as in post-operative period. The procedure could be accomplished without any additional doses of DEXKET. Two of the patients (5%) had post-operative nausea and vomiting. Conclusion: Drainage under sedation by intravenous combination of DEXKET is found to be an effective approach for drainage of abscess in cases of LA.